GAMBARAN PERILAKU MENGGOSOK GIGI PADA SISWA SD KELAS SATU DENGAN KARIES GIGI DI WILAYAH KERJA PUSKESMAS RENDANG KARANGASEM BALI OKTOBER 2014 - I Dewa Gede Bracika Damma Prasada (Intisari Sains Medis, 2016)
The prevalence of dental caries in those with age more than 12 years old in Indonesia reaches 46, 5%. From the prevalence we could see that the majority of students in Indonesia have dental caries. According to RISKESDAS 2007 data, it is said that 91, 1% of Indonesian citizen with age more than 10 years old does brush their teeth every day, but only 7, 3% of them that brush their teeth 2 times a day at the right time which is in the morning after breakfast and at night before bedtime. At Rendang Public Health, dental caries is one of the top 10 diseases of the year 2013. Because of that, this study is done to know the description of tooth brushing habit towards incidence of dental caries because tooth brushing is an important habit for dental caries prevention.